Energetic performance of two different PCM wallboards and their regeneration behavior in office rooms. (September 2017) - Chhugani, Bharat; Klinker, Felix; Weinlaeder, Helmut; Reim, Michaela
Abstract: In order to increase energy efficiency and thermal comfort in lightweight buildings like offices, PCMs (Phase Change Materials) can be integrated within building components like walls or ceilings. The aim of this research is to investigate the thermal behavior of two different PCM wallboards, the Knauf Comfortboard-23 ® and the DuPont Energain ® Board. These wallboards are equipped in the office rooms of the Energy Efficiency Center of ZAE Bayern in Würzburg, Germany. It is evident that the regeneration behavior of PCM wallboards critically influences their thermal performance. Therefore, monitoring data of the years 2015 and 2016 have been evaluated to investigate the regeneration behavior of PCM wallboards under real life conditions. The results show that a sufficient regeneration of PCM wallboards is an issue which has to be addressed to improve the thermal performance. However, PCMs are still well suited to achieve thermal comfort for lightweight buildings in moderate climate zones (e.g. Germany); the room temperature is mostly kept between 22°C to 26°C during summers.